The Interplay of Corporate Image, Service Quality, Customer Value, and Satisfaction in Fostering Customer Loyalty: a Structural Equation Modeling Approach Using SmartPLS - Eugenius Hansel Lee (APPS Publications, 2024)
In today’s hyper-competitive business environment, customer loyalty has become a central focus for organizations aiming to maintain and expand their market share. This study examines the intricate relationships between corporate image, service quality, customer value, and customer satisfaction, and their collective impact on customer loyalty. By analyzing data from multiple scholarly articles and applying a structural equation modeling approach via SmartPLS, this research tests seven hypotheses that explore both direct and indirect effects of these variables on customer loyalty. Results reveal that corporate image, customer value, and satisfaction have significant direct influences on loyalty, while service quality exhibits no direct effect. Satisfaction serves as a mediating variable between corporate image, value, and loyalty, but not for service quality. These findings highlight the nuanced role of satisfaction as a bridge between the perceived value of a brand and customer loyalty. The study concludes with implications for business strategies and recommendations for future research, emphasizing the need to refine loyalty-building approaches by prioritizing customer satisfaction and brand perception.